Single, community-based blood glucose readings may be a viable alternative for community surveillance of HbA1c and poor glycaemic control in people with known diabetes in resource-poor settings. Issue 1 (1st December 2016) - Reidpath, Daniel D.; Jahan, Nowrozy K.; Mohan, Devi; Allotey, Pascale
Abstract : Background: The term HbA 1c (glycated haemoglobin) is commonly used in relation to diabetes mellitus. The measure gives an indication of the average blood sugar levels over a period of weeks or months prior to testing. For most low- and middle-income countries HbA1c measurement in community surveillance is prohibitively expensive. A question arises about the possibility of using a single blood glucose measure for estimating HbA1c and therefore identifying poor glycaemic control in resource-poor settings. Design: Using data from the 2011–2012 US National Health and Nutrition Examination Surveys, we examined the relationship between HbA1c and a single fasting measure of blood glucose in a non-clinical population of people with known diabetes ( n =333). A linear equation for estimating HbA1c from blood glucose was developed. Appropriate blood glucose cut-off values were set for poor glycaemic control (HbA1c ≥69.4 mmol/mol). Results: The HbA1c and blood glucose measures were well correlated ( r =0.7). Three blood glucose cut-off values were considered for classifying poor glycaemic control: 8.0, 8.9, and 11.4 mmol/L. A blood glucose of 11.4 had a specificity of 1, but poor sensitivity (0.37); 8.9 had high specificity (0.94) and moderate sensitivity (0.7); 8.0 was associated with good specificity (0.81) and sensitivity (0.75). Conclusions: Where HbA1c measurement is too expensive for community surveillance, a single blood glucose measure may be a reasonable alternative. Generalising the specific results from these US data to low resource settings may not be appropriate, but the general approach is worthy of further investigation.